2018
DOI: 10.3389/fphys.2018.01360
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationship Between Reduced Blood pH and Acute Pancreatitis: A Translational Study of Their Noxious Combination

Abstract: Acute pancreatitis (AP) is often accompanied by alterations in the acid-base balance, but how blood pH influences the outcome of AP is largely unknown. We studied the association between blood pH and the outcome of AP with meta-analysis of clinical trials, and aimed to discover the causative relationship between blood pH and AP in animal models. PubMed, EMBASE, and Cochrane Controlled Trials Registry databases were searched from inception to January 2017. Human studies reporting systemic pH status and outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 74 publications
(116 reference statements)
1
7
0
Order By: Relevance
“…When base excess < -3.0 mmol/L, the risk of adverse outcomes increase. 21,[31][32][33] In our study, we found that BE lower than −5.2 may be an independent factor for the early prediction of adverse outcomes in AP patients.…”
supporting
confidence: 51%
“…When base excess < -3.0 mmol/L, the risk of adverse outcomes increase. 21,[31][32][33] In our study, we found that BE lower than −5.2 may be an independent factor for the early prediction of adverse outcomes in AP patients.…”
supporting
confidence: 51%
“…A Mouse IL-1β ELISA Kit (EM0109, Wuhan Fine Biotech Co, China) was employed to measure IL-1β levels in serum samples, with absorbance of the samples detected at 405 nm. A semi-quantitative scoring procedure was performed to quantify the edema, necrosis and leucocyte infiltration levels of the hematoxylin–eosin stained slides 40 , 41 . A colorimetric kit was used (Diagnosticum, Budapest, Hungary) to measure serum amylase activity, with absorbance of the samples detected at 405 nm with a FLUOstar OPTIMA (BMG Labtech, Germany) plate reader.…”
Section: Methodsmentioning
confidence: 99%
“…AP is often accompanied by acid-base disturbance. Our earlier work showed the relationship between AP severity and metabolic acidosis ( 38 ). Meta-analyses of clinical studies confirmed that the severity of AP relates to the extent of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%